Pengembangan E-Comic Berbasis Cerita Rakyat Desa Beriang Tinggi Model Cooperative Integrated Reading and Composition dalam Meningkatkan Membaca Pemahaman - Gojali, Denfis; Muktadir, Abdul; Widi Winarni, Endang (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2024)
The aim of this research is to develop an E-Comic Based on the Folklore of Berian Tinggi Village to Improve Reading Comprehension. The type of research used is research and development with the ADDIE model. Instruments include interviews, needs analysis questionnaires, questions, expert validation sheets, user response questionnaires and student response questionnaires. Based on the research results, it can be concluded that the E-Comic developed is suitable for use as class IV Indonesian language content media. The expert validation results were 0.94 from material expert validation, 0.96 from design expert validation, and 0.95 from language expert validation. The user response was very good because the results of the analysis of the class IV teacher questionnaire showed a percentage of 93.75% with very good criteria. Meanwhile, the response from students obtained a percentage of 93% with very good criteria. The e-comic that was developed was effective in improving the reading comprehension of fourth grade students at SD Negeri 44 Kaur. The average value obtained by the experimental class using E-Comic N-Gain was 0.54.